"To be led differently": Neoliberalism, road construction, and NGO counter-conducts in Peru. (August 2015) - Pieck, Sonja K.
Highlights: I examine environmental NGO responses to a large infrastructure project in Peru. I apply the Foucauldian concept of counter-conducts to NGO discourses and practices. The essay shows how NGOs both constitute and challenge neoliberal governmentality. A counter-conducts analysis broadens and further textures ideas of political action. Abstract: This essay explores how neoliberal governance is being contested, adapted, and engaged by Peruvian NGOs responding to the Interoceanic Highway, a large infrastructure project in southern Peru. The road is an anchor project of a continent-wide regional integration effort called IIRSA (Initiative for the Integration of Regional Infrastructure in South America), begun in 2000 and spearheaded by Brazil. IIRSA is a result of Latin America's neoliberal reorientations in the 1980s and 1990s and seeks to facilitate the extraction of resources and the movement of capital. IIRSA has been carried out with very little publicity, but in 2006, a group of non-governmental organizations (NGOs) formed a coalition named the Civil Society Working Group for the Interoceanic Highway, and began critiquing both the road's massive ecological and social consequences as well as the Peruvian government's poorly designed impact mitigation program. Following Foucault, this paper suggests that NGO critique of the IIRSA project represents a form of counter-conduct and at once co-constitutes and challenges neoliberal practices of rule in Peru. Through the lens of "counter-conducts" – defined by Foucault as "the will not to be governed thusly, like that, by these people, at this price" – this essay shows how the NGO working group largely acts within the political space of the state through neoliberal ideas of good governance, while its discourses and actions point to a more profound reworking of environmental politics in Peru, a call in Foucault's words, "to be led differently… and towards other objectives."